The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1242/jeb.158345
|View full text |Cite
|
Sign up to set email alerts
|

Field swimming behavior in largemouth bass deviates from predictions based on economy and propulsive efficiency

Abstract: Locomotion is energetically expensive. This may create selection pressures that favor economical locomotor strategies, such as the adoption of low-cost speeds and efficient propulsive movements. For swimming fish, the energy expended to travel a unit distance, or cost of transport (COT), has a U-shaped relationship to speed. The relationship between propulsive kinematics and speed, summarized by the Strouhal number (St=fA/U, where f is tail beat frequency, A is tail tip amplitude in m and U is swimming speed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…This stems in part from the scarcity of data for unconstrained, volitional swimming. The combined availability of large-volume calibration techniques recently applied to quantify avian flight performance in the field [11] and low-cost underwater cameras has enabled the collection of field performance data for fish [5,12] with higher temporal and spatial resolution than has previously been possible [1]. This approach has revealed the use of intermittent propulsion during routine, sustained locomotion at aerobically sustained speeds and propulsive cycle frequencies, but with insufficient detail to indicate why this swimming style is used [5].…”
Section: Introductionmentioning
confidence: 99%
“…This stems in part from the scarcity of data for unconstrained, volitional swimming. The combined availability of large-volume calibration techniques recently applied to quantify avian flight performance in the field [11] and low-cost underwater cameras has enabled the collection of field performance data for fish [5,12] with higher temporal and spatial resolution than has previously been possible [1]. This approach has revealed the use of intermittent propulsion during routine, sustained locomotion at aerobically sustained speeds and propulsive cycle frequencies, but with insufficient detail to indicate why this swimming style is used [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, animals rarely travel at these maximal speeds, for example, assuming a slower speed when moving undisturbed through their environment while foraging or during dispersal (Wilson et al, 2015). Locomotion is costly (Di Santo et al, 2017;Han et al, 2017), and the energetic cost (cost of transport, CoT) associated with moving at different speeds may impact the speed adopted by an individual (Claireaux et al, 2006;Halsey, 2016). Limited resources may lead to an allocation trade-off so that allocation of energy to locomotion can constrain energy available for other functions (Lailvaux and Husak, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, intermittent swimming in fishes is an example of a potentially energy‐saving behaviour at steady, sustainable swimming speeds (Floryan et al ., 2017; Zhao & Dou, 2020). Field and laboratory observations of volitional swimming fish have demonstrated that fish routinely employ intermittent swimming behaviour during aerobically sustainable swimming (Cathcart et al ., 2017; Ellerby et al ., 2018; Gellman et al ., 2019; Han et al ., 2017; Noda et al ., 2016). Modelling suggests that sustained swimming in an intermittent manner ( i.e ., short duration pulpulsive periods of two to three tailbeats interspersed with ~1.0 s glide periods) reduces the energy costs of locomotion (Floryan et al ., 2017; Zhao & Dou, 2020).…”
Section: Introductionmentioning
confidence: 99%